If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -5 = 7x + 28 Combine like terms: 4 + -5 = -1 -1 = 7x + 28 Reorder the terms: -1 = 28 + 7x Solving -1 = 28 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -1 + -7x = 28 + 7x + -7x Combine like terms: 7x + -7x = 0 -1 + -7x = 28 + 0 -1 + -7x = 28 Add '1' to each side of the equation. -1 + 1 + -7x = 28 + 1 Combine like terms: -1 + 1 = 0 0 + -7x = 28 + 1 -7x = 28 + 1 Combine like terms: 28 + 1 = 29 -7x = 29 Divide each side by '-7'. x = -4.142857143 Simplifying x = -4.142857143
| 5x^2=2-x | | 2y+8=12-6(y+7) | | -4(x-5)+3(a-7)= | | 2-6w-3=9 | | 6x(4x-3x)=92 | | -12(-k)+6=2(-7-k) | | b^2-2b=-a^2+8a | | 4k+5=3k+8 | | Y-7y+6=40 | | 2x-1.3=-1.9 | | b^2-2b+a^2-8a=0 | | 3x+4=4.5 | | 0=0.55t^2-880 | | 2m+3n=d | | 3.3=5.5-0.3x | | -8(-2-12)= | | .66+1=3x-3 | | 12n-4=-13+n-2+11 | | 24-12-k=5 | | 12+6x=1-8x-3 | | 3(-2-20)= | | 4.7+n=-4.7 | | 9(-n-10)=-189 | | 6x+4x+3=92 | | (6x+4x)-3=92 | | 4(6x+3)=92 | | -15+8-10y+1=8 | | 120=37.94+0.50x | | -9x+9=27 | | 6(4x+3)=92 | | 62=3(5)b+2 | | K+3.9=0.7 |